Quantitative Structure-Fluorescence Property Relationship Analysis of a Large BODIPY Library - Schueller, Andreas; Goh, Garrett Benjamin; Kim, Hanjo; Lee, Jun-Seok; Chang, Young-Tae (WILEY-V C H VERLAG GMBH, 2010)
A quantitative structure-fluorescence property relationship (QSPR) analysis of a large 288-membered library based on a single fluorescent BODIPY scaffold is presented for the first time. BODIPY is a versatile fluorescent scaffold with outstanding photophysical properties. Absorption (lambda(abs)) and fluorescence emission (lambda(em)) wavelength maxima were modeled with help of stepwise multiple linear regression (MLR) and support vector regression (SVR). The models were rigorously validated by 10-times 10-fold cross-validation (CV), y-scrambling CV and with an external validation set. Non-linear SVR models (R(2) = 0.92 and Q(2) = 0.71 for lambda(abs); R(2) = 0.89 and Q(2) = 0.69 for lambda(em)) performed significantly better than linear models. A small root mean squared error (RMSE) of 5.62 nm and 11.07 nm was achieved for lambda(abs) and lambda(em), respectively, and confirmed by external validation. A novel intramolecular charge transfer descriptor was developed based on the QSPR analysis and its inclusion in the modeling significantly improved models of lambda(em). We conclude that QSPR is a useful tool for modeling lambda(abs) and lambda(em) of BODIPY fluorophores and suggest QSPR as an ideal partner for the design of compounds with tailored fluorescence properties in a diversity-oriented fluorescence library approach (DOFLA).
Keywords: NEURAL-NETWORKS; SPECTROSCOPIC PROPERTIES; BIOLOGICAL APPLICATIONS; COMBINATORIAL SYNTHESIS; ABSORPTION WAVELENGTH; SPECTRAL PROPERTIES; ROSAMINE LIBRARY; VISIBLE-LIGHT; QSPR METHOD; DYES